Evaluation of Opioid Modulation in Major Depressive Disorder - Ehrich, Elliot (Neuropsychopharmacology, 2015)
Although opioids have known antidepressant activity, their use in major depressive disorder (MDD) has been greatly limited by risk of abuse and addiction. Our aim was to determine whether opioid modulation achieved through a combination of a μ-opioid partial agonist, buprenorphine (BUP), and a potent μ-opioid antagonist, samidorphan (SAM), would demonstrate antidepressant activity without addictive potential. A placebo-controlled crossover study assessed the opioid pharmacodynamic profile following escalating doses of SAM co-administered with BUP in opioid-experienced adults. A subsequent 1-week, placebo-controlled, parallel-group study was conducted in subjects with MDD and an inadequate response to standard antidepressant therapy. This second study evaluated safety and efficacy of ratios of BUP/SAM that were associated with partial and with maximal blockade of opioid responses in the initial study. Pupillometry, visual analog scale assessments, and self-reported questionnaires demonstrated that increasing amounts of SAM added to a fixed dose of BUP resulted in dose-dependent reductions in objective and subjective opioid effects, including euphoria and drug liking, in opioid-experienced adults. Following 7 days of treatment in subjects with MDD, a 1 : 1 ratio of BUP and SAM, the ratio associated with maximal antagonism of opioid effects, exhibited statistically significant improvement vs placebo in HAM-D17 total score (p=0.032) and nearly significant improvement in Montgomery-Åsberg Depression Rating Scale (MADRS) total score (p=0.054). Overall, BUP/SAM therapy was well tolerated. A combination of BUP and SAM showed antidepressant activity in subjects with MDD. Balanced agonist–antagonist opioid modulation represents a novel and potentially clinically important approach to the treatment of MDD and other psychiatric disorders.